Ellipsometric Characterization of Thin Films from Multicomponent Chalcogenide Glasses for Application in Modern Optical Devices - R. Todorov; J. Tasseva; V. Lozanova; A. Lalova; Tz. Iliev; A. Paneva (Advances in Condensed Matter Physics)
A review is given on the application of the reflectance ellipsometry for optical characterization of bulk materials and thin films with thickness between λ/20 and 2λ (at λ=632.8 nm). The knowledge of the optical constants (refractive index, n, and extinction coefficient, k) of thin films is of a great importance from the point of view of modelling and controlling the manufacture of various optical elements, such as waveguides, diffraction gratings, and microlenses. The presented results concern the optical properties of thin films from multicomponent chalcogenide glasses on the base of As2S3 and GeS2 determined by multiple-angle-of-incidence ellipsometry and regarded as a function of the composition and thickness. The homogeneity of the films is verified by applying single-angle calculations at different angles. Due to decomposition of the bulk glass during thermal evaporation, an optical inhomogeneity of the thin As (Ge)-S-Bi(Tl) films is observed. The profile of n in depth of thin As-S-Tl (Bi) films was investigated by evaporation of discrete layers. It is demonstrated that homogenous layers from the previous compounds with controlled composition can be deposited by coevaporation of As2S3 and metals or their compounds (Bi, Tl, In2S3).